2005
DOI: 10.1007/s00024-005-2710-y
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Tremor at Mt. Etna, Italy, Preceding and Accompanying the Eruption of July – August, 2001

Abstract: The July 17 -August 9, 2001 flank eruption of Mt. Etna was preceded and accompanied by remarkable changes in volcanic tremor. Based on the records of stations belonging to the permanent seismic network deployed on the volcano, we analyze amplitude and frequency content of the seismic signal. We find considerable changes in the volcanic tremor which mark the transition to different styles of eruptive activity, e.g., lava fountains, phreatomagmatic activity, Strombolian explosions. In particular, the frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Changes in time and space of background seismic noise related to the volcanic activity are well documented. Falsaperla et al [2005] showed remarkable variation in amplitude and frequency content of the tremor of Mount Etna at seismic stations surrounding the summit crater area before and during the volcanic activity of July -August 2001. During the 2001 flank eruption they observed high tremor amplitude and a shift of the predominant frequencies toward frequencies (about 2 Hz) lower than those of the preeffusive phase.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in time and space of background seismic noise related to the volcanic activity are well documented. Falsaperla et al [2005] showed remarkable variation in amplitude and frequency content of the tremor of Mount Etna at seismic stations surrounding the summit crater area before and during the volcanic activity of July -August 2001. During the 2001 flank eruption they observed high tremor amplitude and a shift of the predominant frequencies toward frequencies (about 2 Hz) lower than those of the preeffusive phase.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2 Hz. During the episodes of FON the signal reached high energy as well, but the spectrum had a broader shape (see also Falsaperla et al 2005). During the PRE stage, spectrograms with yellow to light green tones in the frequency band below 5 Hz, and light blue colours above 5 Hz were typical, due to the lower levels of the seismic energy radiation.…”
Section: Seismic Datamentioning
confidence: 95%
“…2). The strict relationship between eruptive phenomena and volcanic tremor changes was described by Falsaperla et al (2005) and also documented by Alparone et al (2003), who, in particular, analysed high amplitudes of volcanic tremor during vigorous magma jets throughout repeated episodes of lava fountains in 2000. Moving on from these findings, we explored the possibility to reconstruct the Behncke & Neri (2003b).…”
Section: Eruptive Dynamics At Mt Etnamentioning
confidence: 95%
See 1 more Smart Citation
“…The good correspondence between increases of tremor amplitude and summit explosive eruptions (Falsaperla et al 1994(Falsaperla et al , 2005 permitted a retrospective statistical ''forecast'' of lava fountain episodes for the 1989 eruption (Privitera et al 2003) and 1998-99 sequence (Alparone and Privitera 2001). Finally, detailed seismic tremor studies allowed a better characterization of the different eruptive phases occurring during the 2000 lava fountain episodes (Alparone et al 2003).…”
Section: Volcanic Tremormentioning
confidence: 98%